Characterization of Argentinian Honeys Based on their Sugar Profiles and Quality Parameters - Poliero, Aimará Ayelen (2022)
The honeys from the Argentinian provinces of Buenos Aires, La Rioja,Catamarca and Misiones were characterised by the sugar profile (fructose, glucose,sucrose, turanose, maltose and erlose) and the physicochemical parameters (freeacidity, pH, electrical conductivity (EC), colour and contents of moisture, ash,total soluble solids and hydroxymethylfurfural (HMF)) used for honey qualitycontrol. Authentic and traceable honey samples (n = 572) collected along fiveharvests were analysed using the official analytical methods. All honeys met thespecifications of the national and/or international standards for the evaluatedparameters, which denoted the blossom origin of most honeys, and confirmedtheir high quality, good maturity and freshness. The influence of the flora andthe pedoclimatic conditions of each phytogeographical region on the physicaland chemical properties of honey allowed its characterization. Thus, BuenosAires produced typical lighter honeys, and Misiones and Catamarca, darker ones.Buenos Aires honeys presented particular lower values of pH, EC, ash, HMF andmaltose, and higher concentrations of erlose. Misiones honeys exhibited highervalues of moisture, free acidity, EC and turanose amounts, and lower contentsof fructose, glucose and total soluble solids. La Rioja honeys showed higherpH and ºBrix values; and Catamarca honeys, higher sucrose contents. To theauthors? knowledge, the sugar profiles and several quality parameters of honeysfrom Misiones and Catamarca are here reported for the first time, as well as anyphysical and chemical data on La Rioja honeys.